THE ROLE OF CULTURAL EVENT IN A MUSEUM TO THE TOURISTS SATISFACTION AND DESTINATION LOYALTY - Ulinnuha, Hana; Wijaya, Theodora Evelyn; Alanda, Hilwa Shufia (Bogor Hospitality Journal, 2024)
Understanding tourism destination loyaly would be an invaluable benefit for tourism authorities. Especially after the pandemic, tourism authorities are working hard to revive tourism in 2022. Many tourism destinations in Indonesia are gradually implementing various activities to entice tourists to return. As one of the tourism destinations in Indonesia, Surakarta (Solo), whose branding is "The Spirit of Java", is also holding various consecutive events throughout 2023. This research disclosed the role of events in tourists’ satisfaction and destination loyalty, by taking the Rayuan Pulau Kelapa cultural event in Tumurun Museum, Solo, Indonesia, as an empirical example. The purpose of this study was to determine the effect of holding a cultural event in a museum on tourist satisfaction and destination loyalty partially and collectively. According to the findings, the cultural event had an 85.3% and 68.1% impact on visitors' satisfaction and destination loyalty, respectively. In the meantime, destination loyalty is 80.5% influenced by visitor satisfaction. Collectively, the impact of cultural events and tourist satisfaction on destination loyalty was found to be 80.5%.